2021
DOI: 10.1096/fasebj.2021.35.s1.04130
|View full text |Cite
|
Sign up to set email alerts
|

Generating An Exosome Packaged p38 Inhibitory Peptide To Block GPCR Induced Vascular Inflammation

Abstract: A key mediator of angiogenesis and inflammatory response in chronic lung disease is the mitogen‐activated protein kinase (MAPK), p38α. The typical activation pathway for p38α uses MAP kinase kinase 3 (MKK3), and MKK6 to phosphorylate and activate p38α. However, an atypical p38α signaling pathway activated by a family of pro‐inflammatory G‐protein coupled receptors (GPCRs) induces a direct interaction between transforming growth factor β activated kinase 1 binding protein‐1 (TAB1) and p38α, bypassing MKK3/6‐dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research by Kahn et al revealed that EVs derived from various cell sources can transport functional B1 receptors to target cells, thereby promoting the occurrence and propagation of inflammation. 61 Exosomes can also influence innate immune cells and adaptive immune cells by transporting various immune molecules, thereby disrupting the immune homeostasis within the body. Loading PR3 and myeloperoxidase (MPO) into EVs can serve as antigenic stimuli, eliciting an immune response and participating in the immune reactions associated with vasculitis.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Kahn et al revealed that EVs derived from various cell sources can transport functional B1 receptors to target cells, thereby promoting the occurrence and propagation of inflammation. 61 Exosomes can also influence innate immune cells and adaptive immune cells by transporting various immune molecules, thereby disrupting the immune homeostasis within the body. Loading PR3 and myeloperoxidase (MPO) into EVs can serve as antigenic stimuli, eliciting an immune response and participating in the immune reactions associated with vasculitis.…”
Section: Introductionmentioning
confidence: 99%